The emergence of group fitness. (1st August 2022) - Clejan, Iuval; Congleton, Christopher D.; Lerch, Brian A.
Abstract: Whether and how selection can act on collectives rather than single entities has been a tumultuous issue in evolutionary biology for decades. Despite examples of multilevel selection, a simple framework is needed that makes explicit the constraints that lead to the emergence of a "group fitness function." We use evolutionary game theory to show that two constraints are sufficient for the emergence of a well‐defined group fitness, which could even apply to multispecies groups. First, different parts of the group contribute to one another's growth via resources produced proportionally to the density of each resource producer (not the density of the population receiving benefits). Second, invading groups do not share these resources with resident groups. Jointly, these two constraints lead to the "entanglement" of invading individuals' outcomes such that individual fitness can no longer be defined and group fitness predicts evolutionary dynamics through the emergence of a higher level evolutionary individual. Group fitness is an emergent property, irreducible to the fitness of the group's parts and exhibiting downward causality on the parts. By formalizing group fitness as a model for evolutionary transitions in individuality, these results open up a broad class of models under the multilevel‐selection framework.